Persepsi Masyarakat terhadap Kesadaran Muzakki dalam Membayar Zakat di Kabupaten Pinrang - Hj. Muliati; St. Cheriah Rasyid (DIKTUM: Jurnal Syariah dan Hukum, 2019)
This study discussed the public`s perception towards the consciousness of muzakki to paying zakaah in Pinrang Regency. This research objectivewas to know the public perception towards the muzakki`sconsciousness in paying zakaah. This research founded some results as follow: First, the National Zakat Agency of Pinrang Regency has more hard-wired and fairness program according to utilizing of zakaah resource, such as optimal planning and collecting, effective distributing, as well as accountability reporting. Second, the Public perception on a determinant consciousness of muzakki to pay zakaah was more determinate by some results as follows; the religiosity behavior of worship, the Muzakki`s literacy on zakaah obligation, the economic income or wealth factor of Muslim society, the Local Government`s regulation and Muslim Scholar`s role on zakaah literacy, as well as the credibility of National Zakat Agency